Seeing the Urban from the Agrarian: Emerging Forms of Agrarian Urbanization in India - Ankita Rathi (South Asia Multidisciplinary Academic Journal)
Conventionally, the city has been the dominant conceptual basis for understanding urban processes. The rural, on the other hand, is assumed to be external to the city, which is supposedly subsumed by the global forces of capitalist urbanization. Such a conceptualization underestimates the complex ways in which the rural, with its distinct agrarian dynamics of land, labor and capital, is significant in understanding the processes of urbanization that are anchored in geographies beyond the city. Using the framework of “agrarian urbanism” (Gururani 2019), this paper focuses on a small town, Patran, located in the Patiala district of Punjab and argues that contemporary processes of urbanization are deeply entrenched in the rural and its agrarian dynamics of land and caste. By focusing on agrarian changes that were driven by colonial policies of land rights and ownership, and state-led agrarian development strategies in post-independent India, this paper argues that instead of assimilating the rural, urbanization in predominantly agricultural contexts both mirrors and differs from the old forms of agrarian relations and leads to the coproduction of the rural, albeit in new ways.